Pengaruh Pendidikan Kesehatan Menggunakan Media Tiktok terhadap Tingkat Pengetahuan Remaja Putri mengenai Personal Hygiene saat Menstruasi - Alisa Diva Azzahra; Emi Lindayani; Ayu Prameswari (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Adolescence is a phase of maturation of reproductive organs called puberty, one of the signs of puberty in women is menstruation. During menstruation, cleanliness such as personal hygiene needs to be paid attention to so that in the future you don't experience serious problems with the reproductive organs. To reduce this problem, what needs to be done is to provide health education with educational videos via social media Tik Tok. The aim of this research is to determine the effect of health education through social media Tik Tok on increasing knowledge of young women regarding reproductive health, personal hygiene during menstruation at SMAN Rancakalong. This research method uses quantitative research with a quasi-experimental approach with a one group pre test and post test design. The sample in this study was 70 using a simple random sampling technique consisting of grade 10 and 11 female students at SMAN Rancakalong. The results of the research using the Wilcoxon test showed a significant influence between students' knowledge before and after being given health education via social media Tik Tok with a significance value of <0.005 with the median pre-test score being 70.00 and 95.00 for the post-test score. From the results of this research, it can be concluded that the use of social media Tik Tok for health education about personal hygiene during menstruation can increase the knowledge of female students at SMAN Rancakalong.